Efficiency loss breakdown for synchronous rectification scheme for automotive applications - Dimitrios Sarafianos; Danilo X. Llano; Richard McMahon; Timothy Flack; Stephen Pickering (The Journal of Engineering, 2019)
This article presents a synchronous rectification scheme using a six-phase Lundell alternator and a bespoke MOSFET-based active rectifier. The control of the alternator-rectifier system is divided into the hysteresis DC-link voltage control and the switching pattern algorithm. The first allows to keep the DC-link voltage at the required 14V level, while the latter reproduces the same switching pattern as that of a passive rectifier. The system is tested at three different speeds and the results are compared against the body diodes of the MOSFETs in the active rectifier. The harmonic analysis of the generated waveforms indicates the capability of the control algorithm to generate the same switching pattern of a passive rectifier. Finally, the efficiency measurements illustrate a significant efficiency improvement using a synchronous rectification scheme and MOSFETs with low on-resistance.